Factors associated with producing a scientific publication during medical training: evidence from a cross-sectional study of 40 medical schools in Latin America [version 2; peer review: 2 approved] - Valladares-Garrido, Mario J. (2022)
“Background: Scientific publication during medical training is key to promoting enduring cutting-edge knowledge. The promotion of science among medical students in Latin America is a multisectoral issue that is hampered by the lack of governmental knowledge to invest in national research, as well as by the lack of support from local universities. This study aims to determine the factors associated with the production of a scientific publication during medical training among Latin American medical students of local scientific societies. Methods: This is a secondary data analysis of a cross-sectional study conducted in 2016 that assessed the use of information and communication technologies (ICTs) among medical students from 40 local scientific societies of medical students affiliated with FELSOCEM. Teams from each local scientific society surveyed self-reported scientific publications and explored their association with socioeconomic, academic, and research training conditions. We applied nested models to identify the covariates associated with selfreported scientific publication, obtaining a parsimonious mixedeffects multilevel model grouped by medical scientific society. Results: Of 11,587 participants, the prevalence of scientific publications increased in 36% among medical students affiliated to a Scientific Society of Medical Students [parsimonious prevalence ratio (pPR)=1.36, 95%CI=1.16–1.59], 51% among medical students with advanced English proficiency [pPR=1.51, 95%CI=1.21 – 1.87], 85% among medical students who attended a scientific writing skills course [pPR=1.85, 95%CI=1.59–2.15], 81% among medical students who use Sci-Hub [pPR=1.81, 95%CI=1.50–2.20], and 108% among medical students who have access to a pirated academic account [pPR=2.08, 95%CI=1.83–2.36]. Conclusions: Producing a scientific publication among medical students is associated with being affiliated to a scientific society of medical students, English proficiency, training in scientific writing, use of Sci-Hub, and pirated academic accounts. The results will help clinical educators and medical programs improve resources for training students in high-quality research“